Ist die Energiewende sozial gerecht? - Peter Heindl; Rudolf Schüßler; Andreas Löschel (Wirtschaftsdienst, 2014)
Die Energiewende umfasst neben dem Ausstieg aus der Atomenergie unter anderem auch den Ausbau erneuerbarer Energien, die Steigerung der Energieeffizienz und die Senkung des Treibhausgasausstoßes. Dabei wird viel Geld bewegt und es stellt sich immer dringender die Frage nach der sozialen Gerechtigkeit, wenn bereits heute mehr als 17% der privaten Haushalte durch Energiekosten stark belastet sind. Energiearmut wird damit in Deutschland zu einem neuen sozialpolitischen Phänomen. – – The transition of the German energy system towards renewable energy carriers triggers considerable costs for private households. Costs are passed through to households by a surcharge per kilowatt hour. This effectively leads to high cost burdens for poorer households relative to wealthier ones. The authors discuss the issue from the perspective of social justice and argue that costs are distributed in an unfair manner. In the light of the rising costs of renewable energy promotion, affordability of energy among the poorest should receive increasing attention. Measures of fuel poverty and deprivation with respect to energy could serve as adequate ex-post indicators of non-affordability and should be considered in Germany.
Keywords: D63; I32; Q52; 330; Förderung erneuerbarer Energien; Energieeinsparung; Soziale Folgen; Soziale Gerechtigkeit; Soziale Lage; Privater Haushalt; Deutschland